Wanita 37 tahun P3A0 post-SSTP Atas Indikasi Hidrocephalus dengan Polihidramnion dan Presentasi Bokong - veny anisya; Nurul Islamy; Efriyan Imantika; Rizki Dwi Prasetia; Caesaria Sinta Zuya; Imraatul Husniah; Maharani Amanulloh (Medula, 2021)
Hydrocephalus is an enlargement of the ventricle of the brain as a result of an increase in the amount of cerebrospinal fluid (CSS) caused by an imbalance between its production, circulation and absorption. Sectio caesaria can also be selected for fetal deformity in the form of hydrocephalus because itcan risk tearing of the uterus if the delivering is done by pervaginam. Sectio Caesarea is a surgicalprocedure that aims to deliver a baby by opening the abdominal wall and uterus of the mother. Sectio caesarean sectional is more commonly chosen compared to pervaginam delivery for breech presentation management, where the cause of the incidence of breech presentation is still unknown, but there are several risk factors other than prematurity, namely structural abnormalities of the uterus, polyhidramnion, placenta previa, multiparitas, fetal anomaly (anencephaly, hydrocephalus), and previous history of breech presentation. Hydrocephalus is a health problem that affects the retirement system. Polyhidramnions is a term used to describe the accumulation of excess amniotic fluid, this clinical condition is associated with a high risk of poor pregnancy outcomes. Mrs. S's 37-year-old patient came to give birth with contraction that felt increasingly frequent, 37 weeks pregnant, with the results of ultrasound are polyhydramnion and hydrocephalus. From the physical examination obtained general state: moderate pain; temperature: 36.7 oC; blood pressure: 120/80 mmHg; heart rate: 92x/min; respiratory rate: 18 x/min. On leopold I examination obtained a height of fundus uteri is 40 cm, palpable round, hard, head impression. Leopold II palpable flat long part on the right side of the back impression. Leopold III palpable soft round part, the breech impression. Fetal heart rate 155x/min, fetal estimated weight 4.300 grams. In patients performed secio caesarea on indications of hydrocepalus, polyhydroamnion and breech persentation, so that this patient is diagnosed with P3A0 post sectio caesarea on indications of hypocephalus with polyhidramnion and breech presentation. treatment in these patients post SC is seftriaxone, ketorolac and oxytocin drip.